Development of a human-size magnetic particle imaging device for sentinel lymph node biopsy of breast cancer - Bai, Shi; Gai, Lingke; Zhang, Qinyang; Kang, Yue; Liu, Zhiyao; He, Yuan; Liu, Wenzhong; Jiang, Tao; Du, Zhongzhou; Du, Siyao; Gao, Si; Zhang, Min; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
In this study, a novel human-size handheld MPI system was developed for high-precision detection of sentinel lymph nodes of breast cancer. The system consists of a highly sensitive home-made MPI detection probe, a set of concentric coils pair for spatialization, a solenoid coil for uniform excitation at 8kHz@1.5mT, and a full mirrored coil set positioned far away from the scanning area. The mirrored coils formed an extremely effective differential pickup structure which suppressed the system noise as high as 100dB. The different combination of the inner and outer gradient current make the Field Free Point (FFP) move in the Z direction with a uniform intensity of 0.54T/m, while the scanning in the XY direction was implemented mechanically.The third-harmonic signal of the SPIONs at FFP was detected and then reconstructed synchronously with the current changes. Experiment results showed that the tomographic detection limit was 30mm in Z direction, and the sensitivity was about 10μg Fe SPIONs at 40mm distance with a spatial resolution of about 5mm. In the rat experiment, 54μg intramuscular injected SPIONs was detected successfully in the sentinel lymph node, in which the tracer content was about 1.2% total injected Fe. Additionally, the effective detection time window was confirmed from 4 to 6 min after injection.Relevant clinical ethics are already in the application process.